2005
DOI: 10.1021/jp051542b
|View full text |Cite
|
Sign up to set email alerts
|

Ground and Excited State Dissociation Dynamics of Ionized 1,1-Difluoroethene

Abstract: The kinetic energy release distributions (KERDs) for the fluorine atom loss from the 1,1-difluoroethene cation have been recorded with two spectrometers in two different energy ranges. A first experiment uses dissociative photoionization with the He(I) and Ne(I) resonance lines, providing the ions with a broad internal energy range, up to 7 eV above the dissociation threshold. The second experiment samples the metastable range, and the average ion internal energy is limited to about 0.2 eV above the threshold.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(43 citation statements)
references
References 58 publications
7
36
0
Order By: Relevance
“…This multiple channel F-loss mechanism explains the proposed bimodal kinetic energy release distribution observed for C 2 H 3 F + and 1,1-C 2 F 2 H 2 + , 12,13,42 as the low kinetic energy release modus is a result of the statistical dissociation pathway. Furthermore, directC-state involvement is not necessarily required in threshold photoionization.…”
Section: F-atom Loss From C 2 H 3 Fmentioning
confidence: 69%
See 1 more Smart Citation
“…This multiple channel F-loss mechanism explains the proposed bimodal kinetic energy release distribution observed for C 2 H 3 F + and 1,1-C 2 F 2 H 2 + , 12,13,42 as the low kinetic energy release modus is a result of the statistical dissociation pathway. Furthermore, directC-state involvement is not necessarily required in threshold photoionization.…”
Section: F-atom Loss From C 2 H 3 Fmentioning
confidence: 69%
“…[10][11][12][13] Contrary to F-loss from C 2 F 4 + , detailed kinetic energy release studies have shown that F-loss from C 2 H 3 F + and 1,1-C 2 H 2 F 2 + is, in part, an impulsive process. 11,42 The F-loss threshold ion yield curves were shown to correlate only approximately with the TPES signal, 9 which indicates a complex mechanism with possible Rydberg-state involvement. In contrast to C 2 F 4 + , the state which leads unhindered to F-loss is not the first electronically excited state of the parent ion in the other members of the series.…”
Section: Dynamicsmentioning
confidence: 99%
“…The systematic study of ethylene and of several of its halogen substituted derivatives has been initiated, e.g. for C 2 H 3 Cl [12,13], C 2 H 3 Br [14][15][16] and 1,1-C 2 H 2 F 2 [17,18], or is in progress using the same array of techniques. The vacuum UV spectroscopic data reported on vinyl fluoride are very scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In many cases [22,[37][38][39][40][41][42][43][44], the very simple expression (10) is found to provide a very good approximation to P(ε|E) if the value of the exponent k is adequately chosen. A value of k equal to 1/2 or to 1 is usually found.…”
Section: Mem Expression Of the Actual Kerdsmentioning
confidence: 99%
“…A value of k equal to 1/2 or to 1 is usually found. For electronically adiabatic barrierless reactions studied at not too high energies, the appropriate value of k has been observed to be equal to 1/2 [22,[37][38][39][40][41]43,44]. Then, the actual KERD is related to the prior distribution by the following equation:…”
Section: Mem Expression Of the Actual Kerdsmentioning
confidence: 99%